Loss in normal and superconducting millimetre-wave and submillimetre wave microstrip transmission line - Yassin, G; Withington, S (IEE, 1996)
We compare two techniques for calculating the loss of millimetre wave and submillimetre wave microstrip transmission line. The first method is based on conformal transformations and the second method is based on spectral domain analysis. The calculation of loss, through the spectral domain technique, is made possible by removing the current singularities from the path of integration and defining an effective width, based on loss. We use our technique to predict the behaviour of miniature submillimetre wave superconducting microstrip transmission line.